Global perspectives on the strategic role of marketing information systems - Medina-Quintero, Jose Melchor; Sahagun, Miguel Angel 1972-; Alfaro, Jorge 1963-; Ortiz-Rodriguez, Fernando 1974- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series, 2023)
Global Perspectives on the Strategic Role of Marketing Information Systems communicates the recent advances in marketing information systems. Covering topics such as digital entrepreneurship, international business, and micro and small enterprises, this premier reference source is a cuttingedge resource for marketers, entrepreneurs, business leaders and managers, IT managers, students and educators of higher education, librarians, researchers, and academicians.